MOCVD를 이용한 대면적 CdTe 단결정 박막성장 - 김광천; 정규호; 유현우; 임주혁; 김현재; 김진상 (한국전기전자재료학회, 2010)
We have investigated growth of CdTe thin films by using (As, GaAs) buffer layers for application of large scale IR focal plane arrays(IFPAs). Buffer layers were grown by molecular beam epitaxy(MBE), which reduced the lattice mismatch of CdTe/Si and prevented native oxide on Si substrates. CdTe thin films were grown by metal organic chemical deposition system(MOCVD). As a result, polycrystalline CdTe films were grown on Si(100) and arsenic coated-Si(100) substrate. In other case, single crystalline CdTe(400) thin film was grown on GaAs coated？Si(100) substrate. Moreover, we observed hillock structure and mirror like surface on the (400) orientated epitaxial CdTe thin film.